2009
DOI: 10.1080/17454830701529567
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different emotion terms on the size and colour of children's drawings

Abstract: UK Acknowledgements:The research team would like to thank all of the children and teachers who participated in this project. 2 Effects of different emotion terms on the size and colour of children's drawings AbstractRecent studies have shown that, when an affective characterisation is given to a topic, children adjust the size and colour of those topics in their drawings: children increase the size of drawings of topics characterised as "nice", do not always decrease the size of topics characterised as "nasty"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…In a study by Oya and Ovec (2017), the most commonly used colors in the fear drawings were black, red, brown and yellow. Similar results were found in a study by Burkitt et al(2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a study by Oya and Ovec (2017), the most commonly used colors in the fear drawings were black, red, brown and yellow. Similar results were found in a study by Burkitt et al(2009).…”
Section: Discussionsupporting
confidence: 92%
“…In this context, it is possible to find many studies examining children's drawings in the literature. In this subject, there are some studies such as expressing the inner world of children through drawings; Bati (2012), Bornholt & Ingram (2001), Cherney, Seiwert, Dickey & Flichtbeil (2006), Savas (2014), drawings of children about their emotions; Beck & Feldman (1989), Burkitt, Barrett & Davis (2009), Ovec (2012), Sayil (1998), Thomas & Jolley (1998), reflection of anxiety and fear situations on children's drawings; Burkitt & Newel (2005), Cimen (2009), Fox & Thomas, (1990), Golomb (2004), Guvenc (2005), Inan (2006), Kindap & Sayil (2005), Misailidi & Bonoti (2008), and color selection and use; Bal (2010), Burns & Kaufman (1972), Oya & Ovec (2017).…”
Section: Introductionmentioning
confidence: 99%
“…The process of naming a scribble does not indicate the child's desire to represent reality or his or her recognition of some sort of similarity between the drawing and a random object, but, instead, it would simply indicate that the scribbles have become the symbolical witnesses of experiences with objects experimented by the child, mostly through an affective behavior. This would also mean that children alter the line's quality, color, and shape to express their feelings about certain topics, and that these vary depending on whether they regard them as positive or negative (Burkitt et al, 2009 ).…”
Section: The Line As Gesturementioning
confidence: 99%
“…This was their affect with colours used in pictorial conventions used in colouring books and other media. In their study, children were able to use colours in representing positive and negative characters and emotions (Burkitt, Barrett & Davis, 2009). Ou et al (2010) studied the effect of age on colour emotion and found that for single and light colour pairs and achromatic colours were rated less on emotion scales for old subjects than young observers.…”
Section: Effect Of Agementioning
confidence: 99%